The Framework Agreement on the Bangsamoro : background, challenges and prospects - Macasalong, Marjanie Salic (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This research studies the series of agreements between the Government of the Philippines (GPH) and the Moro Islamic Liberation Front (MILF) to understand the crafting of the Framework Agreement on the Bangsamoro (FAB), an agreement that provides the foundation for a just and lasting peace in Mindanao. The researcher uses historical-analytical method to give clear understanding of the Agreement. This means that the researcher studies and examines the historical background of the subject and gives a corresponding critical and thorough analysis. This method is deemed necessary because FAB would not be fully understood how it was formulated and eventually signed without looking back to the previous agreements. Similarly, FAB's historical background would not be sufficient to convey the message to the public without corresponding analyses. The data for this study are collected both from primary and secondary sources. While primary sources, such as signed agreements, joint communiqué, press releases, resolutions, speeches, government reports, official statistics, and non-government organization's reports are more relied upon in order to present a new course of analyses, secondary sources, such as books, articles, journals, and newspapers, are also significant to help the researcher in analyzing the rapid development in the peace process. After thorough study and analyses, the researcher concluded with both hopes and challenges of the Agreement. For the former, it is expected that upon the implementation of FAB, including the enactment of an enabling law, there will be created a Bangsamoro Government that will give larger room for the Muslims to exercise self-governance. For the latter, the issue of unity among the Muslim leaders, and the containment of the possible “peace spoilers”- both within and without – are among the main obstacles in implementing the Agreement.